ANALISIS DESAIN SISTEM GRID PENTANAHAN PLTU BERAU KALIMANTAN TIMUR 2 X 7 MW - Syamsir Abduh; Mulia Sulistiani (Website, 2014)
To be able to secure and safety the equipment and the workers who work in the power plant area Berau 2 x 7 MW, of course, required the earthing system design quality, reliable and efficient whereby the grounding grid resistance, voltage step and touch voltage according to the calculations contained in IEEE Std 80 -2000. This research will discuss the evaluation of system design with respect to the value of earthing resistance grounding grid, mesh voltage and step voltage. Evaluation parameters - parameters according to calculations published in IEEE Std 80-2000. Results from this study is the need for improvements to the design value of the voltage step and touch voltage is actually one - each 219.03 V and 383.29 V, which is greater than the voltage step and touch voltages are allowed each - amounting to 164.86 V for weight 50 kg; 223.13 V for weights 70 kg and 128.21 V to weight 50 kg; 173.53 V to 70 kg weight. Keywords: grounding system, touch and step voltage, conductor areaSistem pentanahan yang berkualitas, handal dan efisien adalah merupakan persyaratan utama dalam merancang suatu sistem pentahanan untuk dapat mengamankan peralatan dan para pekerja di area pembangkit. Makalah ini bertujuan untuk menganalisis desain Grid Pentanahan PLTU Berau 2x7 MW oleh Konsultan Perencana berdasarkan metode IEEE Std 80-2000. Analisis dilakukan terhadap beberapa parameter berupa luas penampang konduktor, nilai tahanan grid pentanahan tegangan sentuh dan tegangan langkah. Hasil dari penelitian menunjukkan bahwa perlu adanya perbaikan desain dengan nilai tegangan langkah dan tegangan sentuh sebenarnya masing – masing 219,03 V dan 383,29 V, yang lebih besar dari tegangan langkah dan tegangan sentuh yang diperbolehkan masing – masing sebesar 164,86 V untuk bobot 50 kg; 223,13 V untuk bobot 70 kg dan 128,21 V untuk bobot 50 Kg;173,53 V untuk bobot 70 Kg. Kata kunci: Grid pentanahan, Tegangan langkah, Tegangan Sentuh, Luas penampang konduktor